The Role of Maslahah Mursalah in Strengthening Religious Moderation: A Contemporary Approach to Mitigating Radicalism in State Islamic Universities in Indonesia - Agus Hermanto; Gesit Yudha; Siti Nurjanah; Agustiyara (Faculty of Sharia, UIN Jurai Siwo Lampung, 2026)
State Islamic Universities (Universitas Islam Negeri/UIN) in Indonesia function as transformative arenas for the development of Islamic thought and movements that actively counter radicalism and extremist ideologies. This study employs a qualitative approach with an exploratory descriptive design, utilizing a case study methodology. Data were collected through field observations and in-depth interviews with nine purposively selected informants, including the head, secretary, and administrative staff of Ma’had Al-Jami’ah. The data were analyzed using content analysis informed by social theory to capture both normative and practical dimensions of religious moderation. The findings demonstrate that the concept of Maslahah Mursalah plays a central role in shaping the religious moderation programs implemented at Ma’had Al-Jami’ah. This principle serves as a flexible legal-ethical framework that enables Islamic teachings to respond constructively to contemporary social challenges. Core religious subjects—such as theology (ʿaqīdah), ethics (akhlāq), and Islamic law (sharīʿah)—are not taught rigidly but are interpreted contextually to address present-day realities. For instance, the concept of jihad is redefined beyond its narrow association with armed struggle and expanded to include intellectual endeavors (ṭalab al-ʿilm), scientific advancement, and technological innovation. This reinterpretation encourages students to view knowledge production and social contribution as integral forms of religious commitment. This study contributes significantly to the discourse on religious moderation in Islamic higher education by offering empirical insights into institutional strategies that foster moderation, resilience, and responsiveness to contemporary societal issues.